Toward the Integration of Agro-Nursing in Philippine Public Health Systems: A Policy Analysis - Maniago, Jestoni; Ngaya-an, Floreliz; Olivar, Jennifer Joy; Tungcul, Leahleonila; Turingan, Oscar (Al-Hijrah Indonesia, 2026)
Background: The integration of public health and agriculture represents a unique and revolutionary mechanism to create solutions to the problems of malnutrition, hunger and rural health that are prevalent in the Philippines. Purpose: This policy analysis documents the introduction of